2001
DOI: 10.1086/318693
|View full text |Cite
|
Sign up to set email alerts
|

AST/RO Observations of Atomic Carbon near the Galactic Center

Abstract: We present a coarsely-sampled map of the region |l|<=2 degrees, |b|<=0.1 degrees in the 492 GHz 3P1-->3P0 fine structure transition of neutral carbon, observed with the Antarctic Submillimeter Telescope and Remote Observatory (AST/RO). The distribution of C[I] emission is similar on the large scale to that of CO J=1-->0. On average, the ratio of the integrated intensities, I_{C I}/I_{12CO}, is higher in the Galactic disk than in the Galactic Center region. This result is accounted for by the absorption of 12CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 19 publications
4
50
0
Order By: Relevance
“…Recent studies in the Milky Way and nearby galaxies have shown that CO and C I have very similar distributions supporting the interpretation that their emission arises from the same gas volume (Fixsen et al 1999;Ojha et al 2001;Ikeda et al 2002). The results from the carbon line and the CO(3−2) line by the PdBI also support that the molecular gas detected in CO is cospatial with the gas detected in the carbon line, as mentioned in Sect.…”
Section: Excitation Temperature From C Isupporting
confidence: 75%
“…Recent studies in the Milky Way and nearby galaxies have shown that CO and C I have very similar distributions supporting the interpretation that their emission arises from the same gas volume (Fixsen et al 1999;Ojha et al 2001;Ikeda et al 2002). The results from the carbon line and the CO(3−2) line by the PdBI also support that the molecular gas detected in CO is cospatial with the gas detected in the carbon line, as mentioned in Sect.…”
Section: Excitation Temperature From C Isupporting
confidence: 75%
“…Observations of the forbidden fine-structure lines of neutral atomic carbon in the Milky Way and nearby galaxies (Ojha et al 2001, Gerin & Phillips 2000, and references therein) have revealed a close association with CO emission. Because the critical density for excitation of both the [Ci]( 3 P 1 → 3 P 0 ) transition at 492.160 GHz and the ( 3 P 2 → 3 P 1 ) transition at 809.342 GHz is roughly that of CO(1-0), these observations suggest that the CO and [Ci] emission originates in the same volume.…”
Section: Atomic Carbonmentioning
confidence: 96%
“…Early simple plane-parallel modeling of these regions, predicting [C I] just in narrow gas slabs between CO and [C II], generated an initial skepticism on the real usefulness of [C I] transitions as molecular gas tracers, recently overcome by a growing body of theoretical and observational work. Modern PDR models including non-equilibrium chemistry (Stoerzer et al 1997), turbulent mixing (Xie et al 1995;Glover et al 2015), clumpy geometries (Stutzki et al 1998), and the effect of cosmic rays Bisbas et al 2015Bisbas et al , 2017 can better explain the detection of [C I] fully concomitant with CO (1 − 0) and 13 CO over a wide range of conditions, with a surprisingly constant ratio N ([C I])/N (CO) ∼ 0.1 − 0.2 and tightly correlated intensities (e.g., Keene et al 1996;Ojha et al 2001;Ikeda et al 2002).…”
Section: Introductionmentioning
confidence: 99%